A Cross-Sectional Study to Evaluate the Refractive Status and Dry Eye Disease in Cases of Vernal Keratoconjunctivitis - Sanjeev Verma; Urmi Midya; Snehal Kedawat (TNOA Journal of Ophthalmic Science and Research)
Objective: To evaluate newly diagnosed vernal keratoconjunctivitis patients for their symptomatology, refractive errors and presence of dry eye disease along with its severity. Methods: A cross-sectional study was conducted after approval from the institutional ethics committee, among 100 patients of vernal keratoconjunctivitis, according to the inclusion and exclusion criteria. After obtaining informed consent, visual acuity and refraction, tear film break-up time, corneal fluorescein staining and Schirmer test (I and II) were performed. An ocular surface disease index questionnaire was filled out for symptomatic evaluation and was also graded on the basis of their ocular findings. The results were analysed by SPSS software. Results: In our study, the most common symptoms experienced were itching (87%) and redness (79%). Dry eye symptoms were present in 43% of patients with an ocular surface disease index (OSDI) mean score of 11.3 ± 4.67. Out of 100 patients, 45 patients had mild findings and 55 patients had moderate findings of VKC. The mean value of tear film break-up time (TBUT) was 8.15 ± 4.47 (P: 0.539), that of corneal fluorescein staining was 4.18 ± 3.4 (P: 0.885) and those of Schirmer’s test I and II were 13.4 ± 5.9 mm (P: 0.288) and 12.95 ± 5.8 mm (P: 0.615), respectively. Myopia was found to be the most common refractive error (35%) followed by hypermetropia (30%) and astigmatism (10%). Conclusion: The results concluded that patients of VKC showed a mild-to-moderate disease and are associated with dry eye having the values of TBUT, corneal staining and Schirmer test, proving the association. Refractive errors are not present in all patients of VKC but have a positive association with increasing severity of the disease.